Art, cybernetics, and pedagogy in post-war Britain - Sloan, Kate, 1979- author.
1 online resource.
Keywords: This is the first full-length study about the British artist Roy Ascott, one of the first cybernetic artists, with a career spanning seven decades to date. The book focuses on his early career, exploring the evolution of his early interests in communication in the context of the rich overlaps between art, science and engineering in Britain during the 1950s and 1960s. The first part of the book looks at Ascott's training and early work, while the second looks solely at Groundcourse, Ascott's extraordinary pedagogical model for visual arts and cybernetics which used an integrative and systems-based model, drawing in behaviourism, analogue machines, performance and games. Using hitherto unpublished photographs and documents, this book will forge a more prominent place for cybernetics in post-war British art.